COVID-19: COULD NEW CORONA VIRUS INFLICT MORE PAIN ON SRI LANKAN ECONOMY - Manawadu, L.; Wijeratne, V.P.I.S. (International Journal of Research and Analytical Reviews (IJRAR), 2020)
The new corona virus pandemic not only brings unpredictable uncertainties to human life, but also to the global economy. Although every countries over the world are trying to prevent infection by implementing social distance, health hygiene strategies, they are also trying to stabilize the national economic situation by formulating financial intervention measures. The disease, which originated in Wuhan, China, is now marked as a “pandemic” and its epicenter has been transferred to countries such as India, Brazil, UK and the United States. While the country’s main priority in the face of this crisis is people’s health, the economic consequences of COVID-19 must also be taken into account. Experts say this is the most serious economic shock in recent history, ironically unprecedented, and is not caused by any defect in the country’s economic growth. It is very important to be concerned about the ultimate economic impact of new coronavirus on Sri Lankan economy as the transmission dynamics of COVID-19 remain unclear. The paper was basically a desk study involving compilation and examination of information from national and international level research studies and media reports such as newspaper articles featuring the updates on COVID 19. Various Short term and middle term, direct or indirect economic shocks were identified in Sri Lanka due to COVID- 19. It will significantly cause island implications on businesses, investments, tourism, education etc. According to the information of Central bank, the economic failure caused by the new corona virus pandemic will last until the end of 2022. Therefore, it is estimated that by 2023, the world economy will not recover earlier than it is now. Similarity, Sri Lanka can expect some economic growth after 2023. Moreover, recently the people can expect a positive output regarding their future economical chain with new coronavirus outbreak due to some measures and strategies have taken by the government. However, Sri Lanka as a middle income country, the upcoming economic issues cannot be escaped. This finding will important to clear understand of the economic impact of COVID-19 and researches and policy makers can identify and develop proper measures to minimize the future economic shocks of the country.
Keywords: COVID-19, Economic Impact, Pandemic, Economic Growth